2012
DOI: 10.1186/preaccept-1264735770575974
|View full text |Cite
|
Sign up to set email alerts
|

The cost effectiveness of NHS physiotherapy support for Occupational Health (OH) services

Abstract: This pragmatic evaluation of the OHPPP indicated that it was likely to be feasible in terms of service usage and could potentially be cost effective in terms of QALYs. Further, the study confirmed that improving physical health status for musculoskeletal pain patients is important in reducing problems with work capacity and related costs. This study suggests that this type of service could be potentially be useful in reducing the burden of pain and should be further investigated, ideally via randomised control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…In most organizations, health and wellbeing initiatives are not limited to occupational health professionals but also to physiotherapists and psychologists, providing a wide range of resources 6 , 7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most organizations, health and wellbeing initiatives are not limited to occupational health professionals but also to physiotherapists and psychologists, providing a wide range of resources 6 , 7) .…”
Section: Discussionmentioning
confidence: 99%
“…Given the high level of moving and handling injuries affecting employee health and wellbeing in this organization, it is not surprising that employees felt that rapid access to physiotherapy services was a valuable resource. Studies have shown that rapid access to physiotherapy is both clinically and cost effective in dealing with employees presenting with moving and handling injuries 6 , 7) .…”
Section: Discussionmentioning
confidence: 99%
“…Workforce managers have a direct relationship with an occupational health rehabilitation service because as commissioners of the service they are responsible for detailing the provision and cost of the service as required for a particular organization [3]. A gap, however, exists in the literature about what workforce managers understand about the role and responsibilities of physiotherapists providing occupational health rehabilitation services and more specifically if physiotherapists are likely to be commissioned as part of the future provision of vocational rehabilitation services [3].…”
Section: Introductionmentioning
confidence: 97%
“…A gap, however, exists in the literature about what workforce managers understand about the role and responsibilities of physiotherapists providing occupational health rehabilitation services and more specifically if physiotherapists are likely to be commissioned as part of the future provision of vocational rehabilitation services [3]. Workforce managers are aware that many employees using the National Health Service (NHS) in the UK are frustrated about the long waiting times for physiotherapy treatment in primary care clinics [4], yet physiotherapists who provide occupational health rehabilitation services are often commissioned as a last resort or as a "safety-net" for organizations in order to provide care for their employees [3].…”
Section: Introductionmentioning
confidence: 99%
“…Outros estudos corroboram que intervir no primeiro sinal de desconforto diminui a chance da queixa gerar uma incapacidade 70,[110][111][112] . Durante a GL, especificamente, a fisioterapeuta conseguia saber precocemente se alguém estava com alguma nova queixa, encaminhando os trabalhadores para o TF, corroborando os achados de Goldenhar e Stafford (2015) que também indicaram ser a GL o momento propício para avaliar quem está com alguma queixa de dor e tomar as providências necessárias 96 .…”
Section: Discussionunclassified